Przyspieszenia Drgań Skrętnych Cienkościennego Pręta o Profilu Otwartym - Sarna, M. (Engineering Transactions, 1970)
In this paper is given an approximate method of solving the equations of twisting vibration in a thin-walled rod having one plane of symmetry and with a short-term action of a determined torque on one of its ends. The acceleration caused by the twisting motion of the rod is established, and the boundary conditions determined for which the approximate solution can be found.